Tocilizumab monotherapy for large vessel vasculitis: results of 104-week treatment of a prospective, single-centre, open study. (26th October 2019) - Saito, Shuntaro; Okuyama, Ayumi; Okada, Yusuke; Shibata, Akiko; Sakai, Ryota; Kurasawa, Takahiko; Kondo, Tsuneo; Takei, Hirofumi; Amano, Koichi
Abstract: Objective: To evaluate the efficacy and safety of tocilizumab (TCZ) monotherapy for large vessel vasculitides (LVV), including Takayasu arteritis (TAK) and GCA. Methods: Twelve patients with a newly diagnosed LVV (eight GCA, four TAK) were enrolled. One TAK patient withdrew consent, so 11 (eight GCA, three TAK) were analysed in a prospective, open-label study. TCZ (8 mg/kg) monotherapy, without glucocorticoids or immunosuppressants, was administered every 2 weeks for 2 months and then every 4 weeks for 10 months. Patients were followed for 1 year after the final TCZ dose. Complete and partial responses were defined as disappearance or improvement of all clinical symptoms and normalization of CRP. Relapse was defined as the worsening or recurrence of clinical symptoms, increase in CRP attributable to vasculitis, and/or the need for initiation of glucocorticoids and/or immunosuppressants. Poor clinical response described patients who did not fit the definition of complete response or partial response. Results: Complete and partial responses rates were 75/66% and 25/0% in GCA/TAK patients, respectively, at week 24 and week 52. Five GCA patients and one TAK patient remained disease-free for 1 year after therapy. One GCA patient required TCZ discontinuation due to heart failure at week 24. Conclusion: TCZ monotherapy showed a high response rate for newly diagnosed LVV patients, and the majority of patients did not relapse for 1 year after TCZ cessation. Result of this study could help us to understand the crucial role of IL-6 in the pathogenesis of LVV.